People’s Perceptions on Conservation Options and Use Value of a Protected Area in Garhwal Himalaya, India - Bhat, Jahangeer A.; Kumar, Munesh; Negi, Ajeet K.; Todaria, N. P. (Indian Forester, 2012)
The present study was carried out in parts of a protected area of Garhwal Himalaya, namely, Kedarnath Wildlife Sanctuary (KWLS). The main aim of the study was to gather and analyze information from the sanctuary dwellers on conservation of natural resources and its value focusing on the needs of local inhabitants. Ninety three respondents of different age groups from two villages, one located within and the other on the fringe of the sanctuary, were considered for analysis. The respondent’s opinions varied with regard to different conservation issues and their perception towards conservation and the value of wild animals, plants and wildlife sanctuary. Sixty (60%) percent of the respondents considered Kedarnath Wildlife Sanctuary (KWLS) as an effective mechanism in the conservation of flora and fauna while 71% said that local communities contributed much more in conservation efforts prior to declaration of it as a wildlife sanctuary. Fifty seven (57%) percent of respondents think that being a sacred area any kind of disrespect around the vicinity of temple will make deity unhappy and 22% of respondents were of the opinion that the impact as a result of irregularities in climatic conditions can be checked by conserving plant resources. Sixty percent respondents reported damage to agricultural crops by wild animals.